2015
DOI: 10.3413/nukmed-0670-14-05
|View full text |Cite
|
Sign up to set email alerts
|

Determination of vitality of liver lesions by alveolar echinococcosis

Abstract: In comparison to FDG PET-CT, the gold standard for detecting viable lesions by depicting metabolism, CEUS detects viable lesions with high specificity and moderate sensitivity by showing vascularization. CEUS must be regarded as an important tool in monitoring HAE. Dimensions of parasitic lesions are displayed more precisely through CEUS than in B-scan. With currently available methods, CEUS quantification has no benefit in monitoring HAE lesions in daily clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 18 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…and Li et al . also made quantitative comparisons between FDG uptake and contrast-enhanced ultrasonography in AE lesions 26 , 30 . Moreover, Azizi et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Li et al . also made quantitative comparisons between FDG uptake and contrast-enhanced ultrasonography in AE lesions 26 , 30 . Moreover, Azizi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the Kodama classification for MRI data, a comparative study between PET/CT and MRI showed that the presence of microcysts was associated with a significant increase in the metabolic activity detected with PET/CT 28 , 33 . Recent studies that compared contrast-enhanced ultrasonography with 18F-FDG PET/CT have shown a good correlation between FDG uptake and perilesional vascularization 26 , 30 , 31 . In cystic echinococcosis (CE), morphological findings with imaging corresponded to disease activity and could be used to manage treatment 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al 8 showed that angiogenesis could be used as an important indicator for evaluating the biological activity of AE. Some scholars have used contrast-enhanced ultrasound 24,25 and Revolution CT total liver perfusion 26 to evaluate angiogenesis and assess HAE biological activity. Ultrasound is the first choice in HAE evaluation, but it is limited in CAE because of the influence of the skull.…”
Section: Discussionmentioning
confidence: 99%
“…Echinococcus multilocularis eggs enter the intestinal tract of the intermediate host and hatch, reaching the liver through the portal vein and lymphatic vessels [17,18]. The larvae of E. multilocularis grow in an in ltrative manner in the liver, gradually invading the normal liver tissue and the surrounding blood and bile ducts through small vesicles.…”
Section: Pathological and Physiological Basis Of Ceus In The Of Haementioning
confidence: 99%